Needle Tip Culture after Prostate Biopsy: A Tool for Early Detection for Antibiotics Selection in Cases of Post-Biopsy Infection - Cheong, Ian Seng; Tsai, Yuh-Shyan; Kang, Chun-Hsiung; Jou, Yeong-Chin; Chen, Pi-Che; Lin, Chang-Te (Urology Journal, 2020)
Purpose: To investigate biopsy needle tip culture after prostate biopsies for bacteria prediction and antibiotics selection. Materials and Methods: From May 2017 to April 2019, 121 patients who underwent a prostate biopsy were enrolled. All biopsy needle tips were sent for aerobic and anaerobic culture. Patients were divided into positive and negative culture groups. Perioperative data were recorded and compared between the two groups. The culture time and susceptibility of febrile patients were analyzed. Blood cultures were conducted for all patients who experienced fever after biopsy. The time and results of the needle and blood cultures were recoded for descriptive analysis. Results: There were 59 (48.8%) positive needle cultures. Other than fever (p = 0.023), there were no statistical significances in clinical data between the two groups. Fever occurred in eight patients, and seven febrile patients had positive needle cultures, six of whom had positive blood cultures. These six needle and blood cultures were consistent with the susceptibility test results. As compared to the waiting time for blood cultures, target antibiotics were administered at an average of 48.0 h earlier based on needle cultures. None of the patients with positive anaerobic cultures developed a fever, while all eight febrile patients had negative anaerobic cultures. Conclusion: Fevers developed at statistically significant higher rate among those who had positive needle cultures. Needle and blood cultures were consistent with the susceptibility test results. Needle cultures can help us administer target antibiotics earlier to febrile patients without the need to wait for blood cultures.